Uncertainty and Fears Around Sustainability: A Qualitative Exploration of the Emotional Reactions of Dental Practitioners and Dental Care Professionals During COVID-19 - Knights, Jennifer; Beaton, Laura; Young, Linda; Araujo, Mariana; Yuan, Siyang; Clarkson, Jan; Humphris, Gerry; Freeman, Ruth (Frontiers in Oral Health, 2022)
Introduction: Recent cross-sectional surveys have shown the detrimental impact of COVID-19 on the health and well-being of dental practitioners and dental care professionals. This qualitative study complements the growing quantitative evidence base with an in-depth exploration of the lived experiences of those working in primary care dental teams in Scotland. Methods: Focus groups were carried out with primary care dental team members and trainees between July and October 2020. Olsen’s tripartite framework of health service sustainability was operationalised to explore how participants experienced uncertainty and their attempts to sustain dental services. Results: Analysis revealed significant concerns surrounding the sustainability of dental services and dental training programmes as a consequence of the emergency level response to the pandemic. Restrictions on dentistry were seen to be severely impeding desirable clinical outcomes, particularly for the most vulnerable groups. Participants experienced being unable to deliver high quality care to their patients as both confusing and distressing. The capability of the dental health care system to meet a growing backlog of dental need and manage this effectively in a pandemic era was called in to serious question. Ongoing uncertainties were affecting how participants were thinking about their professional futures, with stress about income and employment, along with heightened experiences of professional isolation during the pandemic, resulting in some looking at possibilities for retraining or even considering leaving their profession altogether. Discussion: The impact of the pandemic has produced considerable uncertainty regarding the sustainability of dental services in the medium to longer term. It has also served to expose the uncertainties practitioners grapple with routinely as they attempt to sustain their NHS dental service delivery. Conclusion: This study brings into sharp focus the diversity of challenges, confusions and uncertainties experienced by dental practitioners and dental care professionals during the COVID-19 pandemic and the need for suitable and ongoing measures to be put in place to support their mental well-being.